A Study of the Mismatch Between Native Students’ Counselling Needs and Available Services - Dolan, Cheryl A. (Canadian Journal of Counselling and Psychotherapy, 2007)
This study examined the counselling needs of First Nations youth, living in five major First Nations communities of Cape Breton, Nova Scotia. The following types of counselling needs were identified based on the survey and interview data from 54 subjects: (a) the opportunity to validate their cultural identity, (b) personal and substance abuse counselling, (c) support in transition to provincial schools, (d) academic support, and (e) improved access to counseling services. The majority (57%) of the students reported having never or only once accessed the Native counsellor, while less than 10% of them reported ever accessing the regular school counsellor and 82% stated they would not be welcomed there. The provincial school students perceived significantly less counselling service available to them than did those attending bandbased schools. Practical implications are discussed.